The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1037/h0099533
|View full text |Cite
|
Sign up to set email alerts
|

Research on community support services: What have we learned.

Abstract: This article reports the results of a comprehensive review of published literature related to the essential components of a CSS. Each component is analyzed with respect to its documented need, effective intervention strategies, and cost. The need for the types of services and supports initially conceptualized as a CSS in the mid-1970s has been well documented. Also, prior research has now set the stage for large-scale, long-term, experimental studies of measurable, replicable CSS-type interventions.There is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
0
2

Year Published

1990
1990
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(63 citation statements)
references
References 128 publications
4
57
0
2
Order By: Relevance
“…Research in psychiatric rehabilitation, however, indicates that skills learned for successful functioning in one setting are not necessarily transferable to another (Anthony & Blanch, 1989).…”
Section: Introductionmentioning
confidence: 97%
“…Research in psychiatric rehabilitation, however, indicates that skills learned for successful functioning in one setting are not necessarily transferable to another (Anthony & Blanch, 1989).…”
Section: Introductionmentioning
confidence: 97%
“…L'article de Bertelli, dans ce même numéro de Santé mentale au Québec, décrit la réforme proposée ainsi que sa mise en oeuvre. Cette réforme, qui proposait une solution intégrée aux problèmes identifiés par le comité, s'inspirait en outre du vaste courant de réflexion amorcé depuis une dizaine d'années, tant aux États-Unis (Mechanic et Aiken, 1987 ;Lehman, 1989 ;Talbott et Glick, 1986 ;Wasylenki, 1986 ;Bachrach, 1987 ;Anthony et Blanch, 1989 ;Mechanic, 1991) et en Europe (Thornicroft et Bebbington, 1989 ;Freeman et Henderson, 1991), qu'au Canada (Wasylenki et al, 1992) et au Québec (Comité de la santé mentale du Québec, 1985Québec, , 1986 ; Commission d'enquête sur les services de santé et les services sociaux, 1986, 1988MSSS, 1989). Par ailleurs, la politique de santé mentale du gouvernement du Québec (MSSS, 1989) et les plans régionaux d'organisation de services (PROS) qui en découlaient (CRSSSMM, 1990) modifiaient le rôle des centres hospitaliers dans ce domaine en leur confiant en priorité les services de deuxième ligne, la première devant être assumée par les CLSC, les omnipraticiens et les organismes communautaires.…”
Section: Contexte Et Problématiqueunclassified
“…Studies have shown that close to 80% (Anthony and Blanch 1989;Crowther et al 2001;Marrone et al 1998;Harnois and Gabriel 2000) of people with severe mental illness wishing to work remained unemployed due to an array of programmatic and individual issues (Cook and Razzano 2000;Corbière et al 2005;Wewiorski and Fabian 2004). The programmatic variables of various vocational services and programs have been investigated (Cochrane et al 1991;Trochim et al 1994), with supported employment (SE) initiatives yielding the best results for competitive work integration Cook et al 2005;Corbière and Lecomte 2009;Crowther et al 2001;Twamley et al 2003).…”
Section: Introductionmentioning
confidence: 96%